Pengaruh Tingkat Pendidikan, Pengetahuan dan Locus Of Control terhadap Perilaku Keuangan: Studi Kasus pada Pelaku Usaha di Pusat Grosir Solo - Azizah Viridianingrum; Ratna Damayanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The purpose of the study was to determine the effect of an education level, knowledge, and cus of control on the financial behavior of business actors at the Solo Wholesale Center.This research is included in quantitative descriptive with a population of 88 people, all of which were research samples. The sampling technique used is simple random sampling. Data collection techniques using observation, interview, and questionnaire. The data analysis in this study uses multiple linear regression analysis. Based on the results of the study, it can be concluded: There is a simultaneous and significant influence between the level of education, knowledge, and a locus of the control on the finance behavior of business actors at the Solo Wholesale Center. The level of education has a positive and significant effect on the financial behavior of business actors at the Solo Wholesale Center. The knowledge has a positive and significant effect on the financial behavior of business actors at the Solo Wholesale Center. A locus of control has a positive and significant effect on the financial behavior of business actors at the Solo Wholesale Center.